Differentially expressed genes against Colletotrichum lindemuthiamum in a bean genotype carrying the Co-2 gene revealed by RNA-sequencing analysis - Jurado, Maria; Campa, Ana; Ferreira, Juan Jose (Frontiers in Plant Science, 2022)
Anthracnose is responsible for large yield losses in common bean crops. RNA-sequencing was used to investigate the differentially expressed genes (DEGs) in response to race 38 of Colletotrichum lindemuthianum in two near-isogenic lines (A25 and A4806) that differ in the presence of a resistance gene located in the cluster Co-2. Their responses were analyzed at different hours after inoculation (0, 24, and 48) and within and between genotypes. In all, 2,850 DEGs were detected, with 2,373 assigned to at least one functional GO term. Enriched GO terms in the resistant genotype were mainly related to functions as a response to stimulus, hormone signaling, cellular component organization, phosphorylation activities, and transcriptional regulation. The region containing the Co-2 cluster was delimited at the end of chromosome Pv11 (46.65–48.65 Mb) through a comparison with the SNP genotypes, obtained using ‘Genotyping by Sequencing’, among seven resistant lines harboring the Co-2 gene and the susceptible line A25. The delimited region contained 23 DEGs, including 8 typical R genes, that showed higher expression levels in the resistant genotype and non-changes in the susceptible genotype after inoculation. Six R genes encoding protein kinases and an LRR domain formed a cluster in a core region between 46.98–47.04 Mb. The alignment of the raw transcriptome reads in the core region revealed structural changes that were used to design four new breeder-friendly DNA markers, and it revealed some alignments with the intergenic regions, suggesting the presence of genes in addition to those annotated in the reference genome.